2012
DOI: 10.1038/ijo.2012.75
|View full text |Cite
|
Sign up to set email alerts
|

Low doses of grape seed procyanidins reduce adiposity and improve the plasma lipid profile in hamsters

Abstract: The use of GSPE at low doses protects against fat accumulation and improves the plasma lipid profile in hamsters. We suggest that GSPE exerts these effects in part through the activation of both β-oxidation and the GL/FFA cycle, mainly in the RWAT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
71
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 60 publications
8
71
0
1
Order By: Relevance
“…The ability of foods rich in polyphenols, including grapes, to prevent obesity-mediated inflammation or related disorders has been demonstrated [reviewed in 25]. For example, grape seed procyanidin extract supplementation reduces body weight gain and WAT mass in hamsters fed a HF diet [42]. Additionally, mice fed a HF diet supplemented with muscadine grape phytochemicals rich in anthocyanins had decreased body weights, less lipid accumulation in the liver, and improved glucose tolerance compared to HF controls [43].…”
Section: Discussionmentioning
confidence: 99%
“…The ability of foods rich in polyphenols, including grapes, to prevent obesity-mediated inflammation or related disorders has been demonstrated [reviewed in 25]. For example, grape seed procyanidin extract supplementation reduces body weight gain and WAT mass in hamsters fed a HF diet [42]. Additionally, mice fed a HF diet supplemented with muscadine grape phytochemicals rich in anthocyanins had decreased body weights, less lipid accumulation in the liver, and improved glucose tolerance compared to HF controls [43].…”
Section: Discussionmentioning
confidence: 99%
“…Among polyphenols, procyanidins, a family of flavonoids, have been shown to exhibit many healthy beneficial effects against body fat gain [25], dyslipidaemia and atherosclerosis [8], inflammation [26] and insulin resistance [27]. We have recently demonstrated that these polyphenols can also exert metabolic programming effects, demonstrating that the maternal intake of grape seed procyanidins (GSPE) at 25 mg kg −1 of body weight/day, which approximately mimics the average human consumption of procyanidins in Spain [28], increased the adiposity and improved the inflammatory response in 30-day-old male offspring of rats that were fed a HFD during pregnancy and lactation [20].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, our group and others have reported many healthy beneficial effects of a grape seed procyanidin extract (GSPE) (rich in monomers and oligomers of flavan-3-ols, the most abundant polyphenols in the human diet), on different pathologies clustered within the metabolic syndrome, such as insulin resistance, dyslipidaemia, obesity, hypertension and inflammation (Del Bas et al 2005;Pinent et al 2006;Quesada et al 2009;Bladé et al 2010;Terra et al 2011;Belcaro et al 2013;Caimari et al 2013). Interestingly, some studies have shown that polyphenols, which may be isolated or included in extracts or foods, such as olive oil and cocoa, are also able to regulate the gene expression profiles of PBMCs (Konstantinidou et al 2009;Khymenets et al 2009;Camargo et al 2010;Crescenti et al 2013;Tomé-Carneiro et al 2013;van der Velpen et al 2013).…”
Section: Introductionmentioning
confidence: 99%